The contest for a community diagnostic laboratory contract in New Zealand: The influence of neo-liberalism in the public health sector - Brunton, M.; Pick, David (Maney Publishing, 2014)
Introduction: The purpose of this paper was to examine the management of contracting for a diagnostic laboratory health service for the Auckland region in New Zealand, using the concept of governmentality. Methods: Our aim is to provide an overview of a recent case of neoliberal policy implementation, to illustrate how unintended and costly policy outcomes can occur. Results: Despite the effort of government to improve management of the public health sector, analysis of this case reveals the potentially disruptive effects and costs of neo-liberal reform policy. Conclusions: In this study, the costs of neo-liberal reform appear to have unintentionally prevailed over benefits for those the system was designed to serve. Contribution to knowledge: This research has practical implications in that it provides insight into potential and costly outcomes when implementing public health service policy. © W. S. Maney & Son Ltd 2014.